Single-dose bNAb cocktail or abbreviated ART post-exposure regimens achieve tight SHIV control without adaptive immunity - Shapiro, Mariya B. (Nat Commun, 2020)
Vertical transmission accounts for most human immunodeficiency virus (HIV) infection in children, and treatments for newborns are needed to abrogate infection or limit disease progression. We showed previously that short-term broadly neutralizing antibody (bNAb) therapy given 24 h after oral exposure cleared simian-human immunodeficiency virus (SHIV) in a macaque model of perinatal infection. Here, we report that all infants given either a single dose of bNAbs at 30 h, or a 21-day triple-drug ART regimen at 48 h, are aviremic with almost no virus in tissues. In contrast, bNAb treatment beginning at 48 h leads to tight control without adaptive immune responses in half of animals. We conclude that both bNAbs and ART mediate effective post-exposure prophylaxis in infant macaques within 30–48 h of oral SHIV exposure. Our findings suggest that optimizing the treatment regimen may extend the window of opportunity for preventing perinatal HIV infection when treatment is delayed.